Gestation period and certain parturition traits in sows of different genetic groups - HARICHANDAN RAY, S K; SINHA, A K; SINGH, S K; SINGH, BALARAJ (The Indian Journal of Animal Sciences, 2014)
Studies on certain reproductive traits were made in 8 genetic groups of sows covering parameters like gestation length, parturition characteristics and litter traits at birth and weaning. The gestation length was significantly longest in Landrace (114.59 Â± 0.11 days) and shortest (111.90 Â± 0.30 day,) in desi sows and tended to differ significantly among parities and genetic groups. The night farrowing was significantly higher than the day farrowing. The litter size at birth had a high and positive correlation (P<0.01) with tumid teat count and weighr of the foetal membrane.